1993
DOI: 10.1093/oxfordjournals.humrep.a137938
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology: The effect of flutamide on pulsatile gonadotrophin secretion in hyperandrogenaemic women

Abstract: The pulsatile gonadotrophin secretion in hyperandrogenaemic women was examined, following short-term androgen antagonism induced by flutamide, a specific androgen receptor blocker. Flutamide was administered to seven hyperandrogenaemic women and five normal cycling women, at a dose of 250 mg on the evening of day 1, followed by daily doses of 750 mg for 6 days. Blood samples were collected at 10 min intervals for 8 h before (day 1) and during treatment (days 2 and 6). Gonadotrophin and prolactin concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Androgen infusions did not alter LH pulse frequency in women with PCOS, 31 and shortterm ( 1 month) treatment with the androgen receptor blocker flutamide did not alter basal LH pulse patterns in women with PCOS or normal controls. 32,33 However, an indirect effect of HA is suggested by the ability of flutamide to restore sensitivity of the GnRH pulse generator to suppression by E2 and P (Fig. 1).…”
Section: Neuroendocrine Effects Of Androgens In Pcosmentioning
confidence: 99%
“…Androgen infusions did not alter LH pulse frequency in women with PCOS, 31 and shortterm ( 1 month) treatment with the androgen receptor blocker flutamide did not alter basal LH pulse patterns in women with PCOS or normal controls. 32,33 However, an indirect effect of HA is suggested by the ability of flutamide to restore sensitivity of the GnRH pulse generator to suppression by E2 and P (Fig. 1).…”
Section: Neuroendocrine Effects Of Androgens In Pcosmentioning
confidence: 99%
“…However, several studies have suggested that androgens exert a paradoxical effect on gonadotropin secretion in women with PCOS. In particular, (sub)chronic blockade of androgen receptors by flutamide appears to blunt LH pulsatility in PCOS (10,39), which supports the thesis that hyperandrogenemia impairs estrogen and progesterone negative feedback restraint of LH release in these patients (17,34) and in experimental animal models of the syndrome (14). In this scenario, a reduction of testosterone concentrations would be expected to reduce pulsatile LH secretion in women with PCOS by enhancing hypothalamic feedback sensitivity to estrogens/progesterone.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, flutamide administration to hyperandrogenic women is followed by a decrease in LH pulse amplitude associated with an apparent decline in mean LH concentrations. [29][30][31] Androstenedione concentrations significantly decrease during flutamide administration, while sex-hormone-binding globulin and estradiol are not affected. 31 On the other hand, reduction in estradiol alone via treatment with aromatase inhibitors does not alter LH significantly and in fact increases LH pulse amplitude and frequency slightly in association with increased androgens.…”
Section: Why Is There Lh Excess In the First Place?mentioning
confidence: 99%
“…[29][30][31] Androstenedione concentrations significantly decrease during flutamide administration, while sex-hormone-binding globulin and estradiol are not affected. 31 On the other hand, reduction in estradiol alone via treatment with aromatase inhibitors does not alter LH significantly and in fact increases LH pulse amplitude and frequency slightly in association with increased androgens. 32 Furthermore, in patients with androgen secreting ovarian neoplasms, LH is high but returns to normal after tumor removal.…”
Section: Why Is There Lh Excess In the First Place?mentioning
confidence: 99%